2010
DOI: 10.1007/s10886-010-9773-7
|View full text |Cite
|
Sign up to set email alerts
|

Subterranean Herbivore-induced Volatiles Released by Citrus Roots upon Feeding by Diaprepes abbreviatus Recruit Entomopathogenic Nematodes

Abstract: Herbivore-induced volatile emissions benefit plant hosts by recruiting natural enemies of herbivorous insects. Such tritrophic interactions have been examined thoroughly in the above-ground terrestrial environment. Recently, similar signals have also been described in the subterranean environment, which may be of equal importance for indirect plant defense. The larvae of the root weevil, Diaprepes abbreviates, are a serious pest of citrus. Infestations can be controlled by the use of entomopathogenic nematodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
185
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(193 citation statements)
references
References 42 publications
8
185
0
Order By: Relevance
“…To date, few additional tritrophic interactions implying belowground VOCs signaling have been described both in agricultural systems Stelinski 2010, 2011;Rasmann et al 2005) and in wild environment (Rasmann et al 2011). Ali, Alborn, andStelinski (2010) have demonstrated that citrus roots upon feeding by the root weevil Diaprepes abbreviates emit several terpenes in the surrounding soil. Using belowground olfactometers Ali et al (2010) could show that the entomopathogenic nematode Steinernema diaprepesi was significantly more attracted by citrus roots induced by the insect pest larvae than by roots mechanically damaged or by control empty pots.…”
Section: Belowground Tritrophic Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, few additional tritrophic interactions implying belowground VOCs signaling have been described both in agricultural systems Stelinski 2010, 2011;Rasmann et al 2005) and in wild environment (Rasmann et al 2011). Ali, Alborn, andStelinski (2010) have demonstrated that citrus roots upon feeding by the root weevil Diaprepes abbreviates emit several terpenes in the surrounding soil. Using belowground olfactometers Ali et al (2010) could show that the entomopathogenic nematode Steinernema diaprepesi was significantly more attracted by citrus roots induced by the insect pest larvae than by roots mechanically damaged or by control empty pots.…”
Section: Belowground Tritrophic Interactionsmentioning
confidence: 99%
“…Ali, Alborn, andStelinski (2010) have demonstrated that citrus roots upon feeding by the root weevil Diaprepes abbreviates emit several terpenes in the surrounding soil. Using belowground olfactometers Ali et al (2010) could show that the entomopathogenic nematode Steinernema diaprepesi was significantly more attracted by citrus roots induced by the insect pest larvae than by roots mechanically damaged or by control empty pots. However, Ali et al (2011) recently pointed out that insect induced roots of citrus tree could also attract the phytopathogenic nematode Tylenchulus semipenetrans (see above section).…”
Section: Belowground Tritrophic Interactionsmentioning
confidence: 99%
“…Van Tol et al (2001) reported that the nematode Heterorhabditis megidis Poinar, Jackson and Klein 1987 (Rhabditida: Heterorhabditidae) was attracted considerably more strongly to exudates released from roots of the Thuja occidentalis L. conifer when it was attacked by larvae of the Otiorhynchus sulcatus (Fabricius, 1775) (Coleoptera: Curculionidae) beetle. Ali et al (2010 and demonstrated that multiple species of entomopathogenic nematodes are highly attracted to the roots of citrus plants damaged by the feeding of Diaprepes abbreviatus (Linnaeus) (Coleoptera: Curculionidae) larvae. Roots infested and damaged by insects were more attractive to nematodes than those that were mechanically damaged or by the larvae alone.…”
Section: A B Cmentioning
confidence: 99%
“…9 Root-produced volatiles appear to play an important role in the recruitment of EPN [10][11][12][13] and one such volatile, (E)-β-caryophyllene (EβC), has recently been identified for maize roots 14 and was found to be an ideal belowground alarm signal. 15 EPN efficacy can be improved by exploiting the ability of WCR-damaged maize roots to emit the attractant.…”
Section: Diabrotica Virgifera Virgiferamentioning
confidence: 99%